Metode Perbandingan dalam Studi Islam: Analisis Konsep, Praktik, dan Kontribusinya terhadap Pengembangan Keilmuan - Falisha Ramadhani; Mumtazah Nawar Afifah; Mukmin Mukmin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study examines the comparative method in Islamic studies, focusing on its conceptual framework, practical applications, and contributions to contemporary scholarly development. Using a qualitative desk research approach with content analysis, the study critically reviews classical and modern authoritative sources. The comparative method is positioned as an epistemological tool for systematically analyzing similarities and differences in Islamic thought systematically and objectively. The discussion explores its application across various disciplines, including Islamic jurisprudence, Qur'anic exegesis, hadith studies, and the intellectual dialogue between theology, philosophy, and Sufism. The findings demonstrate that diversity in Islamic thought is not arbitrary but rooted in different methodological approaches, historical contexts, and epistemic frameworks. The comparative method plays a crucial role in mapping intellectual diversity, reducing sectarian bias, and fostering constructive academic critique. Furthermore, it contributes to intellectual renewal by enabling Islamic studies to address contemporary challenges such as modernity, pluralism, and digital transformation. Ultimately, the comparative approach strengthens Islamic studies as a critical, inclusive, and responsive academic discipline while maintaining its epistemological integrity. Keywords: Comparative method, Islamic studies, intellectual diversity, scientific objectivity, methodological renewal